Contaminated faucets and sinks as a reservoir for antibiotic-resistant bacterial transmission in healthcare settings - Li, Qiao; Ding, Honghui; Chen, Zhongju; Li, Wenyuan; Tan, Kun; Xu, Chuan; Zou, Mingjun; Wang, Xiao; Tan, Li (The Journal of Infection in Developing Countries, 2025)
Introduction: Multidrug-resistant bacterial infection has emerged as a global hygiene threat in hospitals, and outbreaks cause increased patient morbidity and mortality in the healthcare system. Mounting evidence points to faucets and sinks as the culprits in the outbreaks of multidrug-resistant bacterial infections. However, the mechanism and the route through which faucets and sinks contribute to antibiotic-resistant bacterial transmission are not fully understood. Methodology: We collected 455 surface samples from faucets and sinks in over 60 areas covering four environmental classes to comprehensively overview the prevalence and distribution of multidrug-resistant bacteria in the hospital. Results: We detected 32 carbapenem-resistant Acinetobacter samples, one methicillin-resistant staphylococcus aureus sample, and three carbapenem-resistant Klebsiella pneumoniae samples. Thirteen carbapenem-resistant Acinetobacter spp. and one Klebsiella spp. were identified in the 455 faucet samples. Conclusions: Some faucets in the hospital were contaminated with antibiotic-resistant Acinetobacter, suggesting the possibility that the contaminated faucets and sinks act as a reservoir of antibiotic-resistant bacterial transmission. The current study assessed the prevalence and distribution of multidrug-resistant bacteria on the faucets and sinks in the hospital. It revealed the potential of faucets and sinks as a carrier of antibiotic-resistant bacteria, assisting in spreading them. Improvement of hand hygiene facilities to prevent antibiotic resistance deserves better attention. This study can further instruct us on a surveillance strategy to be used in hospitals.